THE ANALYSIS OF POSITIVE VERBAL REINFORCEMENT OF PRE-SERVICE TEACHER IN EFL CLASSROOM - Maria Fatima Kolo; Imanuel Kamlasi (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2020)
The objective of the study was to find out the types of positive verbal reinforcement used by an English pre-service teacher in the EFL classroom. The study used a qualitative method. This study involved an English teacher and students as participants. The researcher used tape video recording to get the data; transcription and codifying techniques were used to analyze the data. The result showed that the teacher used three types of verbal reinforcement namely words, phrases, and sentences. The researcher found out 27 words, 22 phrases, and 10 sentences of verbal reinforcement used by a teacher in the EFL classroom.